2014
DOI: 10.14503/thij-13-3164
|View full text |Cite
|
Sign up to set email alerts
|

Bileaflet versus Posterior-Leaflet-Only Preservation in Mitral Valve Replacement

Abstract: In the present study of mitral valve replacement, we investigated whether complete preservation of both leaflets (that is, the subvalvular apparatus) is superior to preservation of the posterior leaflet alone. Seventy patients who underwent mitral valve replacement in our clinic were divided into 2 groups: MVR-B (n=16), in whom both leaflets were preserved, and MVR-P (n=54), in whom only the posterior leaflet was preserved. The preoperative and postoperative clinical and echocardiographic findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
1
13
0
3
Order By: Relevance
“…Studies have demonstrated that the integrity of the mitral valve also plays a key role in maintaining right ventricular function [6]. After Lillehei et al reported good results with the posterior leaflet preservation technique in 1964 [1], subsequent studies demonstrated that the anterior leaflet and subvalvular tissue are equally important in protecting the left ventricular function when compared to the posterior leaflet [7, 8]. Gomes conducted a study of both leaflet preservation techniques [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the integrity of the mitral valve also plays a key role in maintaining right ventricular function [6]. After Lillehei et al reported good results with the posterior leaflet preservation technique in 1964 [1], subsequent studies demonstrated that the anterior leaflet and subvalvular tissue are equally important in protecting the left ventricular function when compared to the posterior leaflet [7, 8]. Gomes conducted a study of both leaflet preservation techniques [9].…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, необходимость максимального сохранения нативного митрального комплекса вполне очевидна. Итогом реализации представленного хирургического подхода, помимо восстановления замыкательной функции МК, является обеспечение фазы изоволюмического сокращения, что, согласно результатам ряда исследований, приводит к улучшению или полной нормализации региональной и общей сократимости ЛЖ [18,19]. Вместе с тем, следует отметить некоторые моменты, ограничивающие возможности широкого использования данной методики митрального протезирования.…”
Section: Discussionunclassified
“…Postoperative bleeding was another morbidity in our study leading to requirement of RCC transfusion was significantly high in the nonpreservation group; group A <group B <group C. Similar high level of postoperative bleeding was reported in previous resereach 3 . The concept of preservation was highly recommended in the recent era of cardiovascular surgery, not only preservation of the posterior leaflet & apparatus but the anterior leaflet & its subvalvular apparatus is also important for the improvement of LV functions 18 .…”
Section: S719mentioning
confidence: 99%